Seed Transmission of Epichloë Endophytes in Lolium perenne Is Heavily Influenced by Host Genetics - Gagic, Milan; Faville, Marty J.; Zhang, Wei; Forester, Natasha T.; Rolston, M. Philip; Johnson, Richard D.; Ganesh, Siva; Koolaard, John P.; Easton, H. Sydney; Hudson, Debbie; Johnson, Linda J.; Moon, Christina D.; et al. (Frontiers in Plant Science, 2018)
Vertical transmission of symbiotic Epichloë endophytes from host grasses into progeny seed is the primary mechanism by which the next generation of plants is colonised. This process is often imperfect, resulting in endophyte-free seedlings which may have poor ecological fitness if the endophyte confers protective benefits to its host. In this study, we investigated the influence of host genetics and environment on the vertical transmission of Epichloë festucae var. lolii strain AR37 in the temperate forage grass Lolium perenne. The efficiency of AR37 transmission into the seed of over 500 plant genotypes from five genetically diverse breeding populations was determined. In Populations I-III, which had undergone previous selection for high seed infection by AR37, mean transmission was 88%, 93% and 92%, respectively. However, in Populations IV and V, which had not undergone previous selection, mean transmission was 69% and 70%, respectively. The transmission values, together with single nucleotide polymorphism data obtained using genotyping by sequencing for each host, was used to develop a genomic prediction model for AR37 seed transmission. The predictive ability of the model was estimated at r = 0.54. While host genotype contributed greatly to differences in AR37 seed transmission, undefined environmental variables also contributed significantly to seed transmission across different years and geographic locations. There was evidence for a small host genotype by environment effect, however this was less pronounced than genotype or environment alone. Analysis of endophyte infection levels in parent plants within Populations I and IV revealed a loss of endophyte infection over time in Population IV only. This population also had lower average tiller infection frequencies than Population I, suggesting that AR37 failed to colonise all the daughter tillers and therefore seeds. However, we also observed that infection of seed by AR37 may fail during or after initiation of floral development from plants where all tillers remained endophyte-infected over time. While the effects of environment and host genotype on fungal endophyte transmission have been evaluated previously, this is the first study that quantifies the relative impacts of host genetics and environment on endophyte vertical transmission.